Proyecto técnico y económico para la creación de una planta recicladora de neumáticos (llantas) en el cantón Quevedo, año 2014 - Plúa Panta, Carlos Alberto (2015)
The target of the present investigation is that of there realizes the economic technical study for the creation of a plant recycling plant of tires used in the cantón Quevedo, for effects of the investigation there was realized a survey that took the small craftsmen as a sample vulcanizadores and the companies that devote themselves to the sale and installation of tires in Quevedo, giving like result that the canton does not exist a process adapted to reject the tires, existing a quantity of 2.490 rims that are rejected to the municipal dump on the part of these craftsmen and companies. Inside the technical study. The location of the project was established in the route Quevedo-Valencia inside the road Quevedo circle, a capacity of the plant was estimated in 300 kilos of tires for hour, in addition to realizing the functional flow chart, the production process was defined with its respective flow chart, which indicates the consecutive steps of the recycling of tires out of use. Also there was realized the calculation of the 400 m² civil construction inside this area there was estimated wine vaults of completed product and raw material (Nfus) offices and area of production. There was established the distribution of the plant of the machineries and teams, offices etc. Economic study determined the investment in the project of USD $464.362,25 and she will find products such as: machinery, civil engineering, loan, working capital and 5% contingency, were established annual costs and annual revenue that served as the basis for an effective flow, within financial indicators were determined: take 13.87%, the positive VAN de 111.448,26 , The relation benefit/cost in 1.61, 17,15% TIR, a break-even point in units produced of 28.113 kilos of recycled rubber monthly. Based on these results it was established that the project is technical and economically profitable and the raised hypothesis is accepted, The project of creation of a plant tires recycling plant influences positively the environment of the canton Quevedo.